The Internationalization of Ahlussunnah Wal Jama’ah Preaching: A Study on the Sufistic Movement of KH Ali Tungkal in Southeast Asia - Saidina Usman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Southeast Asia, in particular, has preserved the scientific and Islamic teachings of Ahlussunnah Waljama'ah. One prominent figure who contributed to spreading Ahlussunnah Waljama'ah was KH Ali Tungkal. This study aims to address the following: (1) the characteristics of KH Ali Tungkal's da'wah; (2) the continuity and changes in KH Ali Tungkal's da'wah; and (3) the importance of internationalizing the da'wah of Ahlussunnah Waljama'ah in Southeast Asia. Employing character study methods and qualitative approaches, along with interviews and documentation techniques, this research seeks to answer these questions. The results indicate that (1) the characteristics of Ali Tungkal's da'wah involve the use of the Tarekat Qadariyah wa Naqsyabandiyah (TQN) order. This strategy successfully attracted numerous Muslim figures in Malaysia and Singapore. Oral and written da'wah methods complemented the Sufi approach to da'wah; (2) the continuity and changes in KH Ali Tungkal's da'wah have been passed down continuously to his children and santri, who have spread across Singapore, Malaysia, and Thailand; and (3) the urgency of internationalizing Ahlussunnah Waljama'ah Islam with a spirit of tolerance serves as a benchmark for KH Ali Tungkal in the context of spreading Islam